Analisis Program Literasi Sekolah Terhadap Kemampuan Menyusun Teks Argumentasi Pada Siswa Kelas X MA Al-Amiriyyah - Ahmad Bagas Setiawan; Ali Manshur (PT. ALHAFI BERKAH INDONESIA, 2024)
This study aims to analyze the effectiveness of school literacy programs in improving the ability of MA AL-Amiriyyah students to compose argumentative texts. The method used is qualitative research, involving in-depth interviews with teachers and students, as well as classroom observations. The results of the study indicate that a structured and interactive literacy program significantly improves students' understanding of the structure and important elements in composing arguments. Students showed improvements in writing skills, where they were able to construct more logical and coherent arguments, and support their opinions with relevant data and information. Students' active involvement in group discussions and presentations encouraged them to participate actively and increased their confidence in expressing their opinions. In addition, support from parents and the community proved important in increasing student motivation, creating a conducive learning environment. Formative assessments provided constructive feedback that helped students understand the strengths and weaknesses in their writing skills. Thus, the literacy program not only improved the skills of writing argumentative texts, but also equipped students with critical thinking skills needed in everyday life. This study provides important insights into the implementation of effective literacy programs in the context of modern education.